Users perception of cryptocurrency system application from the Islamic views - Al-hussaini, Abulfathi; Abubakar, Adamu; Noordin, Mohamad Fauzan; Mohd Mohadis, Hazwani (2019)
Cryptocurrency is a peer-to-peer digital exchange system that uses cryptography to generate and distribute token. It is based on an encrypted, peer-to-peer network that facilitates digital barter. By using a cryptocurrency, users are able to exchange value digitally without third party oversight. In regard to the Islamic perspective of cryptocurrency, Muslim scholars and Shari’ah experts have developed varied opinions, some considering it to be permissible (halal) and others prohibited (haram). Among those scholars who consider it to be legally impermissible put forward their reasons, some of them arguing that it violates the constitutions of their governments. On the other hand, there are Muslim scholars who regard cryptocurrency as permissible in principle. Furthermore, there are many uncertainties related to the implementation of the cryptocurrency reported by many researchers and mentioned in the respective fatwas. A number of empirical studies have acknowledged the fact that cryptocurrency, from the Islamic perspective, constitutes the focus of most ongoing research work. Therefore, this current paper seeks to examine the user’s perception of cryptocurrency system application from the Islamic views. The paper utilized qualitative research approach by conducting interviews in order to determine the user perceptions of the system. The interview data gathered were analyzed. The findings indicate that there is lack of Islamic law on the basic criteria for the use of cryptocurrency as either a legal or illegal machinery transaction tool. Hence, Islamic digital currency model is necessary for applying Islamic law to the use of cryptocurrency.